The Impact of Company Size, Interest Income and Risk-Taking on Bank Performance in Indonesia - Yeriko Bagas Christianto; Reza Muhamad Winarto; Intan Nibras Fahar; Henny Setyo Lestari; Farah Margaretha (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the effect of company size, interest income, liquidity risk, and credit risk on bank performance in Indonesia. Using secondary data from banking companies listed on the Indonesia Stock Exchange during 2018-2023, this study applies purposive sampling techniques and panel data regression analysis with Eviews 10 software. The results show that company size and interest income have a positive effect on bank performance, while liquidity risk has no significant effect, and credit risk has a significant effect. This study provides important insights for policymakers and banking practitioners in improving financial performance.